Digital Membership and Activist Strategies in Spanish Non-Statewide Parties - Adrià Mompó (Acta Politologica)
By leveraging new Information and Communication Technologies (ICTs), parties can promote online forms of engagement and multi-speed membership models, innovating in their recruitment strategies and creating new member roles. This paper aims to analyse the introduction of digital enrolment, multi-speed membership options and cyber-activism in Spanish non-statewide parties (NSWPs). Our findings are based on a comparative case study of twelve parties, and data have been collected through interviews with staff members, along with the observation of their recruitment websites and statutes. Most NSWPs in Spain have developed online and multi-speed membership options. The majority of these onlinesupporter roles are focused on campaign volunteering and activism, while democratic engagement is secondary. Moreover, NSWP membership structures present hybrid models, combining online and offline activities. This study contributes to a better understanding of small and regional parties’ membership structures, bringing new evidence about the challenges and possibilities of digital membership beyond mainstream parties.